The Role of Child and Adolescent Adjustment Problems and Sleep Disturbance in Parent Psychological Distress. Issue 3 (4th May 2018) - Chardon, Marie L.; Stromberg, Sarah E.; Lawless, Casey; Fedele, David A.; Carmody, Julia K.; Dumont-Driscoll, Marilyn C.; Janicke, David M.
Abstract : The goal of this study was to examine the moderating role of youth sleep disturbance on the relationship between youth internalizing and externalizing symptoms and parent psychological distress. Participants were 225 youth (ages 8–17) and parent dyads attending a primary care clinic appointment. Participants completed questionnaires that assessed parent psychological distress, youth internalizing symptoms, youth externalizing symptoms, and youth sleep disturbance. Moderation analyses were conducted to examine whether youth sleep disturbance moderated the relationship between youth internalizing and externalizing symptoms and parent psychological distress. The interaction between youth internalizing symptoms and youth sleep disturbance was significantly related to parent psychological distress, such that having increased sleep disturbance amplified the positive relationship between internalizing symptoms and parent psychological distress. The moderation model explained 52% of the variance in parent psychological distress. The interaction between youth externalizing symptoms and youth sleep disturbance was also significantly related to parent psychological distress, such that increased sleep disturbance amplified the positive relationship between externalizing symptoms and parent psychological distress. This model accounted for 53% of the variance in parent psychological distress. Greater youth sleep disturbance strengthens the positive relationship between youth internalizing/externalizing symptoms and parent psychological distress. Accordingly, reducing youth sleep disturbance may serve as an appropriate intervention target in families experiencing increased parent psychological distress.